EKSTRAK BIJI NIMBA Azadirachta Indica A Juss PENGARUHNYA TERHADAP PELETAKAN DAN PENETASAN TELUR ULAT HATI KUBIS Crocidolomia Pavonana F (THE EFFECTS OF NEEM SEED EXTRACT Azadirachta Indica A Juss TO THE OVIPOSITION AND SUPPRESSING EGGS FERTILITY OF Crocidolomia Pavonana F) - Suyanto, Agus; Manan, Abdul (Pembangunan Pedesaan, 2011)
This research aims to determine the effective concentration of neem seed extract in suppressing the oviposition of C. pavonana. This research was conducted at the Laboratory of Pest and Plant Diseases Faculty of Agriculture Unsoed at Purwokerto. The design used was randomized block design. The treatments tested were concentration of neem seed extract 0, 2.5%, 5.0%, 7.5%, and 10.0%. The variables measured were the number of clusters of eggs laid and number of eggs that hatched. The results showed that neem seed extract concentration of 2.5% was effective in suppressing the oviposition of C. pavonana amounted to 84.87% and concentration of 5% was effective in suppressing egg fertility of C. pavonana of 95%.